Acceptance of Artificial Intelligence-Based Online Shopping Applications: A Combination of Artificially Intelligent Device Use Acceptance and Online Shopping Service Quality - Tiffany Ovilia Dwi Lestari; Endang Sugiharti (Journal of Advances in Information Systems and Technology, 2024)
Nowadays, e-commerce, including Shopee, is often associated with Artificial Intelligence (AI). The use of AI systems triggers the emergence of new marketing methods to reach consumers effectively and offer a better shopping experience. Moreover, the increased use of AI in online commerce occurs because AI is considered an excellent tool to meet rapidly changing consumer demands. Currently, more sellers are using AI-supported features such as chatbots, smart logistics, and personalized recommendations. This makes online channels more competitive and enticing for consumers to make purchases. Despite the numerous benefits of e-commerce and AI, they are not exempt from shortcomings that make customers reluctant to use them. Therefore, this research aims to understand the relationship among factors influencing the acceptance and objection of AI-based Shopee by using a combination of Artificially Intelligent Device Use Acceptance (AIDUA) and Online Shopping Service Quality (OSSQ). The study employs a quantitative method with survey data collection techniques. The collected sample from the survey process consists of 169 respondents, mostly females aged 17-26 years, and students. The results obtained find that factors significantly influencing performance expectancy are social influence, hedonic motivation, anthropomorphism, website design, responsiveness, communication, and trustworthiness. Factors affecting effort expectancy are social influence, reliability, communication, anthropomorphism, and website design. Meanwhile, the factor influencing emotion is performance expectancy. Lastly, the factors influencing willingness to use and objection to use are emotion. Based on the research findings, Shopee developers can enhance the quality of their AI programming algorithms and improve the design quality of Shopee.